2011
DOI: 10.1118/1.3592936
|View full text |Cite
|
Sign up to set email alerts
|

Population dose from medical exposure in Taiwan for 2008

Abstract: In the period from 1997 to 2008, the procedure frequency per 1000 population increased by a factor of 2.3 for computed tomography, 2.2 for interventional fluoroscopy, 1.8 for conventional radiography and fluoroscopy, and 1.5 for nuclear medicine. It demonstrated that the medical utilization of imaging facilities raised rapidly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 9 publications
1
14
2
Order By: Relevance
“…Second, we determined that the upper third quartile value (0.311 mSv) of the effective dose is the cut-off value of a high effective dose as there are no previously defined highly effective doses for abdominal digital radiography. Moreover, the upper third quartile value of the effective dose assessed in our study was lower than the mean effective dose reported in other studies (0.44-1.5 mSv) (19,(23)(24)(25)(26).…”
Section: Discussioncontrasting
confidence: 87%
“…Second, we determined that the upper third quartile value (0.311 mSv) of the effective dose is the cut-off value of a high effective dose as there are no previously defined highly effective doses for abdominal digital radiography. Moreover, the upper third quartile value of the effective dose assessed in our study was lower than the mean effective dose reported in other studies (0.44-1.5 mSv) (19,(23)(24)(25)(26).…”
Section: Discussioncontrasting
confidence: 87%
“…The annual effective dose attributed to natural background radiation was about 1.62 mSv [3], and to medical exposures, about 0.74 mSv in Taiwan for 2008 [4]. In 2008, the frequency of CT examinations accounted for only 4.7% of total medical exposures, but the corresponding contribution to the effective dose was as high as 50.8% [4].…”
Section: Introductionmentioning
confidence: 99%
“…In 2008, the frequency of CT examinations accounted for only 4.7% of total medical exposures, but the corresponding contribution to the effective dose was as high as 50.8% [4]. However, the study assumed a CT examination on a patient consisting of a single CT scan, where a scan refers to a single sequence of rotations [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is an unique mandatory health-care system with approximately 100% of the Taiwanese population are enrolled, and covers the vast majority of medical radiation procedures (Chen et al, 2011). A large amount of health-care data are completely collected in the National Health Insurance Research Database (NHIRD).…”
Section: Introductionmentioning
confidence: 99%